Baltic Dry Index as a Major Economic Policy Indicator: The relationship with Economic Growth - Bildirici, Melike E.; Kayikci, Fazil; Onat, Isil Sahin (ELSEVIER SCIENCE BV, 2015)
Since its establishment, the Baltic Dry Index has become one of the foremost indicators on the cost of shipping and an important barometer on the volume of worldwide trade and manufacturing activity. Global factors also play important role in supply and demand of BDI index. BDI and global markets have common economical and financial movement due to market supply and demand which is as a result of turmoil's and crisis. After economic recessions and during economic growth, demand of raw materials increase as production and investments are also increase, as a result transportation volume grows accordingly. On the other hand, during economic slowdowns, demand of raw material decreases which creates utilized capacity. In this paper, MSIAH(3)-VAR(4) model is selected to analyze the relationship between BDI and economic growth for the United States. BDI and GDP are cointegrated for the United States. The crisis regime tends to last 3.13 years on the average, while the Regime 2 is comparatively more persistent with 3.11 years. Finally, Regime 3 which corresponds to the high growth tends to last 2.55 years on the average. Crisis regime of economy is the most persistent regime in the US. Thus, BDI can be used for an indicator of a crisis in GDP growth for the United States.
Keywords: BDI; Markov Switching VAR; Markov Switching Granger Causality; Economic Growth; TIME-SERIES; RATES; MODEL; Business & Economics; Social Sciences - Other Topics